Effects of Seed Treatment on Sudden Death Syndrome Symptoms and Soybean Yield - E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2015)
Sudden death syndrome (SDS) is a soybean disease that perennially limits yields in the Kansas River Valley. The presence of soybean cyst nematode (SCN) and saturated soils have been implicated in contributing to the severity of the disease. Selecting varieties with some degree of tolerance to SDS is the only cultural practice that can potentially reduce the severity of SDS and improve yields. Variety selection alone, however, cannot improve the production of soybeans to make them profitable. The challenge of trying to manage irrigation scheduling to avoid saturated soils further complicates efforts to increase productivity with irrigation while still avoiding SDS. A study with seed treatments applied to soybean was conducted at the Kansas River Valley Experiment Field in 2014, with treatments applied to a soybean variety with a high level of tolerance to SDS. The study was irrigated earlier and more often than normal to promote the disease. The most severely infested plots had more than 50% of the leaf area expressing symptoms of SDS by the R6 growth stage. Treatments with ILeVO from Bayer CropScience (Research Triangle Park, NC) reduced foliar symptoms and increased yields up to 12 bu/a, or more than 25%. These results are similar to those in a 2013 study of varieties with SDS tolerance ranging from very susceptible to more tolerant; the yield increase was up to 16 bu/a, or 40% with the ILeVO seed treatment.
Keywords: soybean sudden death syndrome; seed treatment; soybean yield; Kansas River Valley Experiment Field